Taxonomy of Southeast Asian seaweeds II - Phang, Siew Moi; Lim, Phaik Eem (Monograph series (Universiti Malaya. Institute of Ocean and Earth Sciences), 2013)
This monograph represents the proceedings of the Second Taxonomy of Southeast Asian Seaweed Workshop held at the University of Malaya, April 2010. The monograph contains 12 chapters describing selected genera of the Chlorophyta (Halimeda), Rhodophyta (Kappaphycus, Gracilaria, Gracilariocolax, Gelidiales) and the Phaeophyta (Padina, Sargassum) from the Southeast Asian region.